2019
DOI: 10.1111/puar.13109
|View full text |Cite
|
Sign up to set email alerts
|

Public Policy and Behavior Change

Abstract: Changing behavior is often necessary to tackle societal problems, such as obesity, alcohol abuse, and debt problems. This article has two goals. First, it aims to highlight how governments can try to change the behavior of citizens. Government can use policy instruments to do so, including incentives, bans and mandates, information campaigns, and nudges. However, the government should not be a manipulator that applies policy instruments without societal support. Therefore, the second goal of the article is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 57 publications
1
95
0
2
Order By: Relevance
“…Gelfand et al (2011) have illustrated that the looseness–tightness cultural orientation can impact individuals’ adherence to social norms and subsequently influence their perception of responsibility in state–citizen interactions (Gelfand et al, 2011; Trnka & Trundle, 2014). As suggested by behavioral public administration studies (Tummers, 2019; F. Zhang et al, 2018), the adoption of policy measures across different countries by and large depends on the public’s attitudes, subjective norms, perceived behavioral control, and willingness to cooperate in regard to containing the pandemic (X.…”
Section: Two Critical Contextual Factors: Institutional Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelfand et al (2011) have illustrated that the looseness–tightness cultural orientation can impact individuals’ adherence to social norms and subsequently influence their perception of responsibility in state–citizen interactions (Gelfand et al, 2011; Trnka & Trundle, 2014). As suggested by behavioral public administration studies (Tummers, 2019; F. Zhang et al, 2018), the adoption of policy measures across different countries by and large depends on the public’s attitudes, subjective norms, perceived behavioral control, and willingness to cooperate in regard to containing the pandemic (X.…”
Section: Two Critical Contextual Factors: Institutional Arrangementsmentioning
confidence: 99%
“…Sweden’s COVID-19 response is a good example of a nudge strategy, which is designed to change behaviors without prohibiting options or imposing upon individuals’ freedom of choice, so as to steer people in a particular direction (Hertwig & Grüne-Yanoff, 2017; Tummers, 2019). It ranks the weakest on the stringency index among the four countries.…”
Section: Two Critical Contextual Factors: Institutional Arrangementsmentioning
confidence: 99%
“…In such cases, when recipients perceive that the significant others are supportive of the change, this will positively contribute to their own intentions and subsequent behaviors (Jimmieson et al 2008). The importance of social influence for the interpretation of events in organizational change processes has been strongly recognized in the public administration literature (e.g., Giauque 2015; Kelman 2005; Tummers 2019; Zayim‐Kurtay and Zhu 2019). Tenkasi and Cesmore (2003), for instance, suggested that change management can, and should, capitalize on the social networks in organizations in order to create alliances and power bases that are sources for sense‐making during times of change.…”
Section: Public Sector Reform From a Change Management Perspectivementioning
confidence: 99%
“…Een nudge verbiedt geen opties, zoals een zweep, en verandert de kosten van een keuze niet significant, zoals een wortel. En in tegenstelling tot een preek gaat een nudge niet uit van een perfecte, maar van een begrensd rationeel beslissende burger (Tummers, 2019b). Naast twee zogenaamde harde beleidsinstrumenten (regels en financiële prikkels) verschijnen dan twee zachtere of softere instrumenten: communicatie die inzet op het bewuste, en communicatie die inzet op het onbewuste keuzeproces (House of Lord Report, 2011; Mont et al, 2015).…”
Section: Het Functioneel Perspectief: Nudging Als Beleidsinstrumentunclassified